Dopady COVID-19 na vývoj destinačního managementu v ČR - Holešinská, Andrea (Masaryk University Press, 2022)
Title in English: Impacts of covid-19 on the Development of Destination Management in the Czech Republic The expert study is the output of a research project that focused on the impact of the covid-19 pandemic on destination management. The study presents findings on how destination management organizations (DMOs) dealt with the covid-19 pandemic and how the destination management process in the Czech Republic changed in 2020-2021. At the same time, the study introduces the trends that arose as a reaction of the DMO to the crisis. In the introduction of the study, the theoretical background of destination management is provided to understand the context and to clarify the findings.